Effects of Monensin on metabolic profile and feeding behavior of transition dairy cows - C.R. Mullins; C.E. Moore; H.B. Green; K.L. Perfield (Kansas Agricultural Experiment Station Research Reports, 2011)
Thirty-two Holstein transition cows were used to determine the effects of monensin (Rumensin, Elanco Animal Health, Greenfield, IN; 400 mg/cow daily) on metabolism and feeding behavior. Cows were assigned randomly, based on calving date, to control or monensin treatments (n = 16 per treatment) 21 days before their expected calving date, and cows remained on treatments through 21 days in milk. Feeding behavior and water intake data were collected daily. Blood samples were collected at 8 different time points during the experimental period. Monensin decreased mean and peak plasma ketone concentrations, and also decreased time between meals before and after calving. No effects of monensin supplementation were observed on milk production or other metabolic traits. Furthermore, we observed no treatment effects on disease incidence, although sample size was small for detecting such effects.; Dairy Day, 2011, Kansas State University, Manhattan, KS, 2011; Dairy Research, 2011 is known as Dairy Day, 2011
Keywords: Dairy Day; 2011; Kansas Agricultural Experiment Station contribution; no. 12-176-S; Report of progress (Kansas Agricultural Experiment Station and Cooperative Extension Service); 1057; Monensin; Transition cow; Feeding behavior; Dairy